The Effect of Financial Digitalization on Savings and Cost Reduction in MSME Entrepreneurs in Medan City - Jirwanto, Henry (PT FORMOSA CENDEKIA GLOBAL, 2024)
Limited research has been conducted on the impact of financial digitalization in the context of MSMEs, particularly in the city of Medan. Therefore, this research aims to investigate the impact of financial digitalization on savings and cost reduction in MSME entrepreneurial companies in Medan City. This research uses a research design with quantitative data collected from 89 MSMEs. Quantitative analysis shows a significant positive relationship between financial digitalization and savings and cost reduction in MSMEs. The moderating effects of firm size and technological readiness were also identified, indicating that smaller MSMEs and those with higher technological readiness may gain more benefits from financial digitalization. The findings further support the positive impact of financial digitalization, as MSMEs report increased accuracy and reliability of financial data, faster processing of financial transactions, and reduced manual documentation and record-keeping. However, challenges related to limited financial resources, lack of technical skills, and resistance to change were identified as barriers to implementing financial digitalization in MSMEs.